SGLT2 inhibitors or GLP-1 receptor agonists as second-line therapy in type 2 diabetes: patient selection and perspectives - Gurgle HE; White K; McAdam-Marx C (Vascular Health and Risk Management, 2016)
Holly E Gurgle, Karen White, Carrie McAdam-Marx Department of Pharmacotherapy, University of Utah College of Pharmacy, Salt Lake City, UT, USA Abstract: Controversy exists regarding the selection of second-line therapy for patients with type 2 diabetes mellitus (T2DM) who are unable to achieve glycemic control with metformin therapy alone. Newer pharmacologic treatments for T2DM include glucagon-like peptide-1 receptor agonists and sodium–glucose cotransporter 2 inhibitors. Both the classes of medication are efficacious, exhibit positive effects on weight, and are associated with minimal risk of hypoglycemia. The purpose of this review is to compare the clinical trial and real-world effectiveness data of glucagon-like peptide-1 receptor agonists versus sodium–glucose cotransporter 2 inhibitors related to A1c reduction, weight loss, cost-effectiveness, cardiovascular outcomes, and safety in patients with T2DM. This review summarizes comparative evidence for providers who are determining which of the two classes may be the most appropriate for a specific patient. Keywords: type 2 diabetes mellitus, GLP-1 receptor agonist, SGLT2 inhibitor, A1c, weight loss, adverse effect